The Stewardship of Higher Education Re-imagining the Role of Education and Wellness on Community Impact - Perez, David M. Callejo; Ode, Joshua; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Understanding the entrepreneurial nature of universities$1 (Bin particular, the relationship between education and health in relation to development and wellness of communities$1 (Bthis volume provides a description/narration of the efforts in how universities can address their shifting contexts while engaging their communities in social change. In the development of this book, we have explored how reforms in American higher education are impacting the role of universities and their faculty. Contributors were asked to imagine possibilities for research and outreach by providing salient examples of how higher education can lead and change how we view the role of health and education within institutions and society. Each author writes across common themes that address the problems and possibilities of higher education curriculum and projects aligned with the mission of stewardship. The authors highlight interdisciplinary approaches and projects for faculty work, modification of the Teaching-Research-Service expectations, and community initiatives that can emerge from real-life problems (to impact wellbeing) and create rich and deep research possibilities for practitioners to impact both higher education and society. The process and research approaches used by the authors include imagining the community as part of a process of the change and part of what changes, exploring how community change can build on the strengths of local people, and why community organization and advocacy should revolve around social learning and community capacity theories. Given the diversity of topics and approaches, as editors we have tried to honour both the authors$1 (Bwords and style in expressing their opinions to provide a forum for the readers to envision stewardship.s
Keywords: Education; Education; Education (general).